Document Delivery and Resource Sharing: Global Perspectives - Elham M. Abdallah (14130980) (2023)
This publication is intended to provide librarians, library practitioners, as well as teachers, researchers, and students of universities and research organizations and other interested parties, a foundation in resource sharing principles, practices and management. This publication provides an overview of where things stand today with resource sharing, including key trends, challenges, opportunities, and priorities. The publication seeks to address international resource sharing, exploring the current state of European and international resource sharing systems and the governing laws and regulations and includes case studies and best practices from various countries. The author’s ambition is for it to become a must-read piece in the wider resource sharing world and inspire more libraries to participate in open resource sharing practices both locally and internationally. This publication is Edited by Peter Collins. Other Information Published in: IFLA Professional Reports: 140 License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://repository.ifla.org/handle/123456789/2704